Efficiency of Using the Hydrogen Peroxide Vapor Generator “Fhileas 75” for Disinfection of the Air Ducts of separately Ventilated system for Infected Animal Housing - V. G. Germanchuk; E. V. Kislitsina; О. A. Lobovikova; N. P. Mironova; N. Yu. Shavina; M. V. Gordeeva (Проблемы особо опасных инфекций, 2022)
The aim of the work was to evaluate the efficiency of using the “Fhileas 75” hydrogen peroxide vapor generator for decontaminating the air ducts of the individually ventilated system, “Bio A.S.”, for housing of infected animals.Materials and methods. The hydrogen peroxide vapor generator “Fhileas 75” (France), a disinfectant manufactured by “FHILEASAFE” (7 % hydrogen peroxide solution and 0.15 % peracetic acid solution), separately ventilated system “Bio A.S.” (Germany) for the infected animal housing were applied in the work. Serratia marcescens 9 was used as test-culture.Results and discussion. The efficiency of using the hydrogen peroxide vapor generator “Fhileas 75” for decontamination of air ducts and internal surfaces of the rack of the individually ventilated system “Bio A.S.” on the test-culture S. marcescens 9 at 1·106 mc/ml concentration has been established (operation parameters of the individually ventilated system unit are as follows: air exchange rate – 60 changes per hour, air flow volume – 28 m3/hour, number of disinfection cycles – 5, disinfectant spraying time – 97 min, exposure time – 24 hours).